Lactation curve of cross-bred buffalo under two production systems in the Amazonian region of Brazil - A.C. Ribeiro Neto; A.M.V. Batista; K.R. Santoro; R.G.A. Pereira; S.B.P. Barbosa (Italian Journal of Animal Science, 2010)
This study was conducted at the Agroforestry Research Center of EMBRAPA (CPAFRO), Rondônia, Brazil, to evaluate the lactation curve of crosss-bred buffalo [Murrah (M), Mediterranean (Me) and Jafarabadi(J)] under two production systems. Production system one (PS1) corresponded to the period of 1984 to 1998 where animals (4471 observation) were milked once a day and received only pasture without supplementation. Production system two (PS2) corresponded to the period of 1999 to 2002 where animals (458 observations) were milked twice daily with concentrate supplementation to pasture. Eight mathematical functions were used: Inverse Polynomial, Linear Hyperbolic, Incomplete Gamma, Logarithmic, Logarithmic Quadratic, Linear, Quadratic and Jenkins & Ferrel. Statistical analysis was conducted using PROC NLIN of SAS (2005). Results showed that for both production systems, Incomplete Gama was the best function to describe the lactation curve. Values of coefficient of determination, standard-deviation, coefficient of variation and standard-error were 95%, 0.068, 7.20, and 0.003, respectively. The corresponding values for PS2 were 96%, 0.200, 2.12, and 0.003. Values of the lactation curve parameters (a, b, and c) for PS1 and PS2, respectively, were (a) 7.0035923 and 10.9209, (b) -0.1080043 and -0.1614882, (c) 0.0434868 and 0.0679365.